The Effect of Additional Tomato Extract in Diluting Sodium Citrate and Egg Yellow in Kampung Chicken on The Quality of Semen Cow Limousine - Situmorang, Dian Fatihani; Syukriah, Syukriah; Tambunan, Efrida Pima Sari (Jurnal Biologi Tropis, 2024)
Undiluted sperm will reduce fertility, therefore dilution is performed to maintain the quality of spermatozoa during storage. Tomatoes contain carbohydrates, vitamin A, vitamin C, protein, and lycopene as antioxidants. Carbohydrates and antioxidants act as a source of energy to potentially prevent free radicals that can damage cells. This study aims to determine the effect of adding tomato juice in sodium citrate diluent and free-range chicken egg yolks to the semen quality of limousin cattle. This study used a completely randomized design (CRD) with 4 treatments and 5 replications. The treatment consisted of a solution of sodium citrate and egg yolk (P0), sodium citrate and egg yolk + 10% tomato extract (P1), sodium citrate and egg yolk + 20% tomato extract (P2), and egg yolk sodium citrate + 30% tomato extract. % (P3). Parameters observed were motility, viability and abnormalities of semen spermatozoa of Limousin cattle. Observations were made at 0, 24, 48, and 72 hours after cooling. The results showed that the addition of 10% tomato extract (P1) had a significant effect on the highest percentage of motility, namely 42.00 ± 2.73c for the 48th hour, the highest viability 62.10 ± 4.51c for the 72nd hour, and lowest abnormality 16.60 ± 1.81a until the 72nd hour. The addition of 10% tomato extract (P1) in sodium citrate diluent and egg yolk resulted in the best motility, viability, and abnormality percentage of Limousin cattle spermatozoa.